Factors Associated With Type 2 Diabetes Mellitus In The Productive Age Group (15-64 Years) In The Wajo Community Health Center Work Area, Baubau City In 2025 - Jumadi; Sriwulan; Amiruddin, Eky Endriana (LPPM Universitas Mohammad Husni Thamrin, 2026)
Based on data from the non-communicable disease programmer at the Wajo Health Center in Baubau City, the risk of diabetes mellitus occurs from the age of 15 years and above, in 2020 the number of sufferers was 296 cases and in 2024 it increased with the number of sufferers being 301 cases. In this case the number of cases of diabetes mellitus increased from 2020 to 2024. The aim of the study was to determine the related factors such as knowledge, obesity, physical activity and diet with type 2 diabetes mellitus in productive age (15-64 years) in the Wajo Community Health Center Working Area, Baubau City in 2025. This study employed a quantitative cross-sectional study design. The population comprised 301 productive-age individuals (15-64 years) in Lamangga, Tanganapada, and Wajo sub-districts, with a sample size of 72. The sampling technique used was random sampling with univariate and bivariate analysis. The chi-square test was used. The results showed a relationship between knowledge (p-value = 0.029 < 0.05), obesity (p-value = 0.012 < 0.05), physical activity (p-value = 0.002 < 0.05), and dietary patterns (p-value = 0.000 < 0.05) and the incidence of type 2 diabetes mellitus in the Wajo Community Health Center, Baubau City.